2020
DOI: 10.1007/s10340-020-01250-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of moth sex pheromone precursors in Nicotiana spp.: a worthwhile new approach to pest control

Abstract: Pheromones are environmentally friendly alternatives to traditional pesticides for pest control. They are widely applied for insect monitoring, mating disruption and mass trapping. Nicotiana benthamiana and N. tabacum are potential green biomass production platforms of moth sex pheromones. Using these two Nicotiana species as plant factories, we expressed biosynthetic genes of plant and insect origin in leaf tissue. Moth sex pheromone precursors (E)-11-tetradecenoic acid, (Z)-11-tetradecenoic acid and (Z)-11-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 67 publications
5
38
0
Order By: Relevance
“…The maximum pheromone accumulation levels measured in SxPv1.2 reached 174.5 µg g -1 FW (totalling both alcohol and acetate forms). This is about half of the levels of precursors reported by Ding et al, (2014) in transient experiments (381 µg g -1 ) or by Xia et al, (2020) in stable plants (335 µg g -1 ), and may indicate a partial conversion into biologically active forms, or upper limit for toxicity, especially in the case of Z11-16OH. However, only a small portion of the plant pheromone content can be detected in the environment after a 48h incubation.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…The maximum pheromone accumulation levels measured in SxPv1.2 reached 174.5 µg g -1 FW (totalling both alcohol and acetate forms). This is about half of the levels of precursors reported by Ding et al, (2014) in transient experiments (381 µg g -1 ) or by Xia et al, (2020) in stable plants (335 µg g -1 ), and may indicate a partial conversion into biologically active forms, or upper limit for toxicity, especially in the case of Z11-16OH. However, only a small portion of the plant pheromone content can be detected in the environment after a 48h incubation.…”
Section: Discussionmentioning
confidence: 72%
“…Such toxic effects can hamper plant viability and result in a negative selection pressure against the genotypes with higher pheromone production levels. Interestingly, whereas Xia et al, (2020) found strong deleterious effects associated to the production of (E)-11-tetradecenoic acid, the same authors regenerated normal plants that accumulated Z11-16CoA, the direct precursor of the volatile pheromones produced here. The fact that the simple addition of a desaturase activity leads to deleterious effects may indicate that Z11-16OH itself is responsible for the toxic effects observed when accumulated in leaves.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations